Rapidly changing economic environments and the Wagner's Law: the case of Saudi Arabia - Al-Obaid, Hussain M. A., author; Fan, Liang-Shing, advisor; Fan, Chuen-mei, committee member; Olienyk, John P., committee member; Bernasek, Alexandra, committee member (Colorado State University. Libraries, 2004)
The size of government expenditure has been an issue of debate for decades. The consistent increase in size of government expenditure over the time is attributed to many reasons which lead to appear several models to explain government expenditure growth. More than one hundred years ago Adolph Wagner proposed a positive correlation (known as Wagner's Law) between level of development and growth of public sector. The objective of this study is to determine the nature of relationship between economic growth and government expenditure and its direction by testing the six existing versions of Wagner's Law in the case of Saudi Arabia. The first and the main task of this study is to present data mainly on government expenditure over the period 1970 to 2001. A second task of this study deals with explaining the observed growth of government expenditure. The major hypothesis tested in this respect is Wagner's Law of expanding state activities. The purpose here is to assess as much as possible, the contribution of this law in helping to understand the growth of Saudi Arabia economy. For determining the long-run relationship between total government expenditure and real gross domestic product and its direction, we looked at the time series properties using aggregate time series data of Saudi Arabia for the period 1970-2001. Our results are indicative rather than definitive. We found that the public expenditure and GDP variables were non-stationary in levels, but stationary first differences, that is, they are integrated of order one I(1). According to the test results, there is one co-integration relationship between the variables. Co-integration is essential for the valid test of Wagner's Law. Finally, we used Granger Causality testing procedure to determine the direction of causality. Our conclusion from these tests is that there is Bidirectional causality which is suggested by Wagner's Law from LTEX to LGDP at log difference and log level. Overall the relationship between government expenditure and gross domestic product as hypothesized by Wagner finds statistical support in Saudi Arabia over the period 1970 to 2001. The general conclusion reached in this study is that the Saudi experience supports Wagner's Law.
Keywords: finance; studies; correlation analysis